Prevalence of non-alcoholic fatty liver disease in the Russian Ural Eye and Medical Study and the Ural Very Old Study - Bikbov, Mukharram; Gilmanshin, Timur R.; Zainullin, Rinat M.; Kazakbaeva, Gyulli M.; Iakupova, Ellina M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Gilemzianova, Leisan I.; Khakimov, Dinar A.; Miniazeva, Liana A.; Jonas, Jost B. (Scientific reports, 2022)
Information about prevalence and associated factors of non-alcoholic fatty liver disease (NAFLD) has been scarce for the Russian, Eastern European and Central Asian world region. We assessed prevalence and associated factors of NAFLD in two population-based studies (Ural Eye and Medical Study (UEMS), Ural Very Old Study (UVOS)), which were conducted in rural and urban regions in Bashkortostan/Russia and included participants aged 40 + years and 85 + years, respectively. Defining NAFLD by an absence of regular alcohol consumption, and by abnormally high alanine transaminase (ALT) and aspartate transaminase (AST) concentrations or an AST/ALT ratio of > 1.0, 2341 out of 5852 UEMS participants (40.0%; 95% confidence intervals (CI) 38.8, 41.3) had NAFLD. A higher NAFLD prevalence correlated (multivariable analysis) with older age (odds ratio (OR) 1.02; 95%CI 1.01, 1.03; P < 0.001), female sex (OR 1.87; 95%CI 1.58, 2.21; P < 0.001), higher waist-hip circumference ratio (OR 2.64; 95%CI 1.11, 6.27; P = 0.03), lower depression score (OR 0.98; 95%CI 0.96, 0.999; P = 0.04), higher serum concentrations of creatinine (OR 1.004; 95%CI 1.000, 1.008; P = 0.03) and bilirubine (OR 1.009; 95%CI 1.002, 1.015; P = 0.008), lower prothrombin index (OR 0.99; 95%CI 0.985, 0.998; P = 0.01), lower ankle-brachial index (OR 0.49; 95%CI 0.32, 0.75; P = 0.001), higher prevalence of a grain-rich diet (OR 1.88; 95%CI 1.50, 2.36; P < 0.001) and iron deficiency-related anemia (OR 1.61; 95%CI 1.13, 2.29; P = 0.009), and lower prevalence of vigorous leisure activities (OR 0.84; 95%CI 0.72, 0.99; P = 0.04). In the UVOS, NAFLD prevalence (mean: 789/1130; 69.8%; 95%CI 67.1, 72.3) was associated with female sex (OR 2.24; 95%CI 1.66, 3.01; P < 0.001), higher serum concentrations of low-density lipoproteins (OR 1.34; 95%CI 1.17, 1.55; P < 0.001), lower prothrombin index (OR 0.98; 95%CI 0.96, 0.99; P = 0.002), and lower ankle-brachial index (OR 0.03; 95%CI 0.02, 0.29; P = 0.003). The NAFLD prevalence of 40% in the UEMS and 69.8% in the UVOS corresponds to findings obtained in other world regions and shows the importance of NAFLD, including its determinants such as age, sex, waist-hip ratio, serum creatinine concentration, prothrombin index, ankle-brachial index, and lower physical activity.
Gesehen am 13.02.2024